Bottom Reflooding Experiments in a Thin Rectangular Channel. (September 2017) - Xu, Wei; Yao, Jun; Ji, Jianye; Liu, Xiaojing; Cheng, Xu; Zeng, Wei; Yu, Hongxing
Abstract: Experiments were carried out to study the thermal hydraulic behaviors in a narrow rectangular channel under bottom reflooding conditions. The channel is formed between a stainless steel heating plate and a transparent heatproof glass and dimensions of the channel are 600 mm in height, 60 mm in width and 4 mm of gap thickness. All the parameters (such as initial wall temperature, inlet velocity and systematic pressure) affect the heat transfer features during quenching process. The experimental results illustrate that for a given initial surface temperature, rewetting velocity increases with the increasing flow rate and increasing systematic pressure, while it decreases with the increasing initial surface temperature. With different flow rate and system pressure, the rewetting temperature is almost the same, but it varies when initial surface temperature is different.